2019
DOI: 10.17140/otloj-5-156
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Tuberculosis and Metastatic Undifferentiated Carcinoma of Nasopharynx in Cervical Lymph Node

Abstract: The coexistence of a head and neck cancer and a lymph node tuberculosis is rarely described. The problem is essentially diagnostic. We report the case of a patient with cervical lymphadenopathy and non suspect swelliing of nasopharynx. Histopathological study of lymph node reveled an association of a tubercular adenitis and a metastasis of a squamous cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…7 Mezri et al reported an incident with simultaneous TB and undifferentiated metastatic carcinoma of the nasopharynx, where the diagnostic dilemma is higher. 8 In our case, there were squamous cell carcinoma and TB in both the primary lesion and the cervical lymph nodes. There is a possibility that the disease is carried to the lymph nodes from the primary site, along with metastasis.…”
Section: Discussionsupporting
confidence: 45%
“…7 Mezri et al reported an incident with simultaneous TB and undifferentiated metastatic carcinoma of the nasopharynx, where the diagnostic dilemma is higher. 8 In our case, there were squamous cell carcinoma and TB in both the primary lesion and the cervical lymph nodes. There is a possibility that the disease is carried to the lymph nodes from the primary site, along with metastasis.…”
Section: Discussionsupporting
confidence: 45%